Emerging incidence of Lyme borreliosis, babesiosis, bartonellosis, and granulocytic ehrlichiosis in Australia - Mayne, Peter J (Dove Medical Press, 2011)
BACKGROUND: Borrelia burgdorferi, the causative agent of Lyme disease (LD), and Babesia, Bartonella, and Ehrlichia species (spp.) are recognized tick-borne pathogens in humans worldwide. Using serology and molecular testing, the incidence of these pathogens was investigated in symptomatic patients from Australia. METHODS: Sera were analyzed by an immunofluorescent antibody assay (IFA) followed by immunoglobulin (Ig)G and IgM Western blot (WB) assays. Both whole blood and sera were analyzed for detection of specific Borrelia spp. DNA using multiplex polymerase chain reaction (PCR) testing. Simultaneously, patients were tested for Babesia microti, Babesia duncani, Anaplasma phagocytophilum, Ehrlichia chaffeensis, and Bartonella henselae infection by IgG and IgM IFA serology, PCR, and fluorescent in situ hybridization (FISH). RESULTS: Most patients reported symptom onset in Australia without recent overseas travel. 28 of 51 (55%) tested positive for LD. Of 41 patients tested for tick-borne coinfections, 13 (32%) were positive for Babesia spp. and nine (22%) were positive for Bartonella spp. Twenty-five patients were tested for Ehrlichia spp. and (16%) were positive for Anaplasma phagocytophilum while none were positive for Ehrlichia chaffeensis. Among the 51 patients tested for LD, 21 (41%) had evidence of more than one tick-borne infection. Positive tests for LD, Babesia duncani, Babesia microti, and Bartonella henselae were demonstrated in an individual who had never left the state of Queensland. Positive testing for these pathogens was found in three others whose movements were restricted to the east coast of Australia. CONCLUSION: The study identified a much larger tick-borne disease (TBD) burden within the Australian community than hitherto reported. In particular, the first cases of endemic human Babesia and Bartonella disease in Australia with coexisting Borrelia infection are described, thus defining current hidden and unrecognized components of TBD and demonstrating local acquisition in patients who have never been abroad.